First report of stereotactic body radiotherapy for large-volume spinal tumors - Ito, Kei (Int Cancer Conf J, 2017)
Stereotactic body radiotherapy (SBRT) for spinal metastases is very effective for pain relief and local tumor control. However, high-level evidence is limited to lesions in a single vertebra or in 2 contiguous vertebrae. To clarify the toxicities, we report herein the results of treatment for 4 patients who received SBRT to large-volume spinal tumors. The lesions comprised bone metastasis from renal cancer, local recurrence of rectal cancer invading the spine, osteosarcoma, and giant cell tumor of bone in 1 case each. Tumor volumes ranged from 738 to 1,766 ml. Doses ranging from 24 Gy in 2 fraction to 35 Gy in 5 fractions were delivered. The median follow-up was 24 months (range 4–35 months). Pain reduction was achieved in all patients in 4 weeks after SBRT. The outcomes were partial response in 1 patient, stable disease in 2, and tumor progression in 1. One patient showed grade 3 acute radiation dermatitis 4 weeks after SBRT, and another patient showed grade 3 late radiation dermatitis.